2017
DOI: 10.1080/00029157.2016.1233093
|View full text |Cite
|
Sign up to set email alerts
|

The Hypnotic Induction in the Broad Scheme of Hypnosis: A Sociocognitive Perspective

Abstract: Researchers and clinicians typically divide hypnosis into two distinct parts: the induction and the suggestions that follow. We suggest that this distinction is arbitrary and artificial. Different definitions of hypnosis ascribe different roles to the hypnotic induction, yet none clearly specifies the mechanisms that mediate or moderate subjective and behavioral responses to hypnotic suggestions. Researchers have identified few if any differences in responding across diverse hypnotic inductions, and surprising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…The common theme in hypnotic inductions is that they establish a hypnotic context for the period of time in which suggestions are delivered ( Sheehan and Perry 1976 ; Lynn et al 2017 ). There is evidence that the increase in response to suggestion attributable to hypnotic induction is small ( Braffman and Kirsch 1999 ; see Connors et al 2012 , for an exception), and that any increase in responding over non-hypnotic suggestibility may be attributable to the use of the word ‘hypnosis’ ( Gandhi and Oakley 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common theme in hypnotic inductions is that they establish a hypnotic context for the period of time in which suggestions are delivered ( Sheehan and Perry 1976 ; Lynn et al 2017 ). There is evidence that the increase in response to suggestion attributable to hypnotic induction is small ( Braffman and Kirsch 1999 ; see Connors et al 2012 , for an exception), and that any increase in responding over non-hypnotic suggestibility may be attributable to the use of the word ‘hypnosis’ ( Gandhi and Oakley 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…While evidence for effects on responding is mixed (for a review see Terhune and Cardeña 2016 ), the prevalence of relaxation instructions in hypnotic inductions suggest that a requirement for relaxation might be expected by many and therefore be useful for establishing the hypnotic context ( Lynn et al 2017 ). Therefore, and although relaxation is not a necessary component of hypnotic inductions ( Banyai and Hilgard 1976 ; Cardeña 2005 ), we retained elements of the WSGC relating to relaxation and counting down in order to ensure the induction was long enough to meet participants’ possible expectations.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of inductions have been developed over the years, particularly in clinical practice, which raises the question of whether some induction procedures are more effective than others in enhancing responsiveness to suggestion. Several reviews largely concluded that no systematic evidence points to the utility of some inductions over others (Lynn, Maxwell, & Green, 2017;Terhune & Cardeña, 2016). (e.g., for relaxation), and their reference to outdated, unhelpful concepts (e.g., hypnosis as a sleep-like state) (Shor & Orne, 1962).…”
Section: Myths and Misconceptions About Inducing Hypnosismentioning
confidence: 99%
“…A wide variety of inductions have been developed over the years, particularly in clinical practice, which raises the question of whether some induction procedures are more effective than others in enhancing responsiveness to suggestion. Several reviews largely concluded that no systematic evidence points to the utility of some inductions over others (Lynn, Maxwell, & Green, 2017; Terhune & Cardeña, 2016). Similarly, in a Bayesian re‐analysis of previous studies comparing different types of inductions, Martin and Dienes (2019) primarily found that different inductions were comparable and not reliably different in terms of their efficacy.…”
Section: Myths and Misconceptions About Inducing Hypnosismentioning
confidence: 99%
“…For example, certain theories postulate that the induction yields an altered state of consciousness and the emergence of hypnotic phenomena (59). However, different arguments undermine the notion that induction and suggestions are conceptually distinct (60). First, both induction and suggestion rely on instructions that solely differ in content relative to their respective timing and purpose (61).…”
Section: The Science Of Hypnosismentioning
confidence: 99%